2020
DOI: 10.1017/s1930297500007397
|View full text |Cite
|
Sign up to set email alerts
|

Training choices toward low value options

Abstract: Food decisions are driven by differences in value of choice alternatives such that high value items are preferred over low value items. However, recent research has demonstrated that by implementing the Cue-Approach Training (CAT) the odds of choosing low value items over high value items can be increased. This effect was explained by increased attention to the low value items induced by CAT. Our goal was to replicate the original findings and to address the question of the underlying mechanism by employing ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Some support for the involvement of attention was found in eyetracking studies with CAT, which found that during the probe phase, participants view chosen Go stimuli more 12,13,18,26 , suggesting that increased gaze time during the probe phase indicated attentional evidence-gathering process, which increased the likelihood of choosing the Go stimuli over NoGo stimuli [27][28][29] . However, most of these studies 13,18,26 did not find enhanced gaze for Go stimuli when they were not chosen, undermining the hypothesis that enhanced attention could drive the CAT preference modification effect on its own. However, these previous mechanistic views have focused on the probe phase where preferences are being expressed, whereas preference is changed during the training phase.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some support for the involvement of attention was found in eyetracking studies with CAT, which found that during the probe phase, participants view chosen Go stimuli more 12,13,18,26 , suggesting that increased gaze time during the probe phase indicated attentional evidence-gathering process, which increased the likelihood of choosing the Go stimuli over NoGo stimuli [27][28][29] . However, most of these studies 13,18,26 did not find enhanced gaze for Go stimuli when they were not chosen, undermining the hypothesis that enhanced attention could drive the CAT preference modification effect on its own. However, these previous mechanistic views have focused on the probe phase where preferences are being expressed, whereas preference is changed during the training phase.…”
Section: Introductionmentioning
confidence: 92%
“…Attention has also been shown to play a key role in value-based decision making both on its own and in synergy with memory 24,25 . Some support for the involvement of attention was found in eyetracking studies with CAT, which found that during the probe phase, participants view chosen Go stimuli more 12,13,18,26 , suggesting that increased gaze time during the probe phase indicated attentional evidence-gathering process, which increased the likelihood of choosing the Go stimuli over NoGo stimuli [27][28][29] . However, most of these studies 13,18,26 did not find enhanced gaze for Go stimuli when they were not chosen, undermining the hypothesis that enhanced attention could drive the CAT preference modification effect on its own.…”
Section: Introductionmentioning
confidence: 92%